Eye growth changes in myopic children in Singapore. Issue 11 (18th October 2005) - Saw, S M; Chua, W H; Gazzard, G; Koh, D; Tan, D T H; Stone, R A
Abstract : Aims: To assess the longitudinal changes in biometric parameters and associated factors in young myopic children aged 7–9 years followed prospectively in Singapore. Methods: Children aged 7–9 years from three Singapore schools were invited to participate in the SCORM (Singapore Cohort study Of the Risk factors for Myopia) study. Yearly eye examinations involving biometry measures were performed in the schools. Only myopic children (n = 543) with 3 year follow up data were included in this analysis. Results: The 3 year increases in axial length, anterior chamber depth, lens thickness, vitreous chamber depth, and corneal curvature were 0.89 mm, −0.02 mm, −0.01 mm, 0.92 mm, and 0.01 mm, respectively. Children who were younger, female, and who had a parental history of myopia were more likely to have greater increases in axial length. After adjustment for school, age, sex, race, parental myopia and reading in books per week, the age (p<0.001), sex (p = 0.012), and parental myopia (p = 0.027) remained significantly associated with the 3 year change in axial length. Reading in books per week, however, was not associated with axial length change. Children with faster rates of progression of myopia had greater increases in axial length (Pearson correlation coefficient ( r ) = −0.69) and vitreous chamber depth ( r  = −0.83). Conclusions: The 3 year change in axial length of Singapore children aged 7–9 years at baseline was high and greater in younger children, females, and children with a parental history of myopia. Myopia progression was driven largely by vitreous chamber depth increase.